Quality Measurement Recommendations Relevant to Clinical Guidelines in Germany and the United Kingdom: (What) Can We Learn From Each Other?. (27th March 2018) - Petzold, Thomas; Deckert, Stefanie; Williamson, Paula R.; Schmitt, Jochen
We conducted a systematic review of clinical guidelines (CGs) to examine the methodological approaches of quality indicator derivation in CGs, the frequency of quality indicators to check CG recommendations in routine care, and clinimetric properties of quality indicators. We analyzed the publicly available CG databases of the Association of the Scientific Medical Societies in Germany (AWMF) and National Institute for Health and Care Excellence (NICE). Data on the methodology of subsequent quality indicator derivation, the content and definition of recommended quality indicators, and clinimetric properties of measurement instruments were extracted. In Germany, no explicit methodological guidance exists, but 3 different approaches are used. For NICE, a general approach is used for the derivation of quality indicators out of quality standards. Quality indicators were defined in 34 out of 87 CGs (39%) in Germany and for 58 out of 133 (43%) NICE CGs. Statements regarding measurement properties of instruments for quality indicator assessment were missing in German and NICE documents. Thirteen pairs of CGs (32%) have associated quality indicators. Thirty-four quality indicators refer to the same aspect of the quality of care, which corresponds to 27% of the German and 7% of NICE quality indicators. The development of a standardized and internationally accepted methodology for the derivation of quality indicators relevant to CGs is needed to measure and compare quality of care in health care systems.